Flores comestíveis : tagetes e calêndulas cultivadas com tratamentos agroecológicos de pó-de-rocha e de homeopatia - Dutra, Claudia Braga (2016)
The present form of commercial production of flowers is an activity that practices the use of pesticides and chemical fertilizers because of the quality requirements for marketing. However, in organic and agroecological production, there is the use of agroecological alternative inputs that do not cause damage to the environment and human health. The objective of this work is to enable the cultivation of edible flowers in agroecological system. The Tagetes spp cultivation of flowers and Calendula spp in organic production system used basalt powder, Giga Mix® and homeopathic compound as alternative treatments by evaluating the number of flowers and buds, floral diameter, height. The experiments were conducted in the open, in an area of the University of Passo Fundo, in the summer (Tagetes) and winter (Calendula) following in 2014/2015. The seedlings of Tagetes spp and Calendula spp, coming from particular producer, biweekly were treated after transplantation with homeopathic compound 9 CH (Proximate Hahnemanianna): Arnica montana, Calcarea carbonica, Carbo vegetalis, Sulphur and Silicea. The second experiment tested treatments of rock dust on the plants. The design was a randomized block in a factorial design (2x3) two Tagetes spp and three powder treatments rock, GigaMix® and witness, and the factorial (2x2) with and without application of homeopathic compound and two varieties of Tagetes spp, with five repetitions. In winter, he repeated the same factor schemes for both calendula experiments. All treatments maintained the same standard and quality of production. Treatment with commercial powder GigaMix®favored the hybrid Tagetes erecta cultivation increasing the floral diameter and basalt powder favored the number of buttons/plant Tagetes patula tricolor "Summer Mix". The use of homeopathy has provided increased floral diameter Calendula officinalis 'aprotic' Thus, the use of such alternative technologies in the cultivation of edible flowers in a agroecological system proved to be feasible within the current context of commercial floriculture.